Stabilizing and Destabilizing Agents in Laptop Orchestra Improvisation - Tsabary, Eldad (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2016)
The purpose of this study is to explore effective strategies for successful collective improvisation in laptop orchestras. Collective music-making requires listening to and interacting with others in order to create a cohesive performance. However, musical expression also involves a sense of agency (Maus 1991; Levinson 2004), which may be perceived most prominently when individuals take temporary creative leadership roles and intentionally destabilize the sense of cohesion, either to rejuvenate it or to catalyze change. In my experience teaching and directing the Concordia Laptop Orchestra (CLOrk), I have observed that orchestra members learn to be attentive to stabilization and cohesion and to apply those concepts to their music-making relatively quickly, but that they have more difficulty learning and applying destabilization and catalysis techniques. Through interviews and questionnaires with CLOrk members, I have learned that the obstacles to taking destabilizing actions while improvising may be technical (primarily monitoring challenges), personal (ego depletion and attentional limits), and/or social (risks of peer rejection, exclusion, and shame). CLOrk members proposed strategies to address these challenges, including (1) arranging the orchestra in subgroups to improve audio monitoring coherence and to reduce attentional load and (2) communicating regularly about all relevant matters, including emotional and social obstacles in order to promote a mindful environment of sharing and a safe space for trial and error in the creative process.